Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1038/s41401-021-00700-w
|View full text |Cite
|
Sign up to set email alerts
|

ATF3 contributes to brucine-triggered glioma cell ferroptosis via promotion of hydrogen peroxide and iron

Abstract: Ferroptotic cell death is characterized by iron-dependent lipid peroxidation that is initiated by ferrous iron and H2O2 via Fenton reaction, in which the role of activating transcription factor 3 (ATF3) remains elusive. Brucine is a weak alkaline indole alkaloid extracted from the seeds of Strychnos nux-vomica, which has shown potent antitumor activity against various tumors, including glioma. In this study, we showed that brucine inhibited glioma cell growth in vitro and in vivo, which was paralleled by nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 46 publications
2
59
0
2
Order By: Relevance
“…Increased endoplasmic reticulum stress is linked to ferroptosis, which upregulates the production of activated transcription factors (ATFs). Recent research has discovered that ATF3 can bind to the promoter of SLC7A11 , suppressing its expression and system Xc–transport function (which prevents lipid peroxidation and protects cells from nonapoptotic, iron-dependent death), resulting in reduced GSH production, increased free Fe 2+ , and lipid peroxidation accumulation, and ultimately causing DNA, protein, and lipid membrane damage ( Wang et al, 2020 ; Lu et al, 2021 ). Furthermore, ATF3 is a well-known marker of sensory neuron injury, with up-regulated expression found in the DRG and spinal cord in chronic pain models ( Ding et al, 2020 ; Wang K et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increased endoplasmic reticulum stress is linked to ferroptosis, which upregulates the production of activated transcription factors (ATFs). Recent research has discovered that ATF3 can bind to the promoter of SLC7A11 , suppressing its expression and system Xc–transport function (which prevents lipid peroxidation and protects cells from nonapoptotic, iron-dependent death), resulting in reduced GSH production, increased free Fe 2+ , and lipid peroxidation accumulation, and ultimately causing DNA, protein, and lipid membrane damage ( Wang et al, 2020 ; Lu et al, 2021 ). Furthermore, ATF3 is a well-known marker of sensory neuron injury, with up-regulated expression found in the DRG and spinal cord in chronic pain models ( Ding et al, 2020 ; Wang K et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…ATF3 was reportedly a versatile transcriptional factor involved in multiple biological processes like cell death. [47][48][49][50] More importantly, as a common stress sensor, ATF3 could directly bind to the promoter of SLC7A11 to suppress its transcription and thereby result in lipid peroxidation and ferroptosis after the stimulation with erastin. 50 Consistent with previous reports, our data showed that both the mRNA and protein levels of ATF3 were significantly increased in response to either erastin/ RSL3 monotreatment, and were further upregulated after combined treatment with IFN-γ in melanoma cells (figure 7B,C).…”
Section: Mir-21-3p Increases the Efficacy Of Anti-pd-1 Immunotherapy ...mentioning
confidence: 99%
“…[47][48][49][50] More importantly, as a common stress sensor, ATF3 could directly bind to the promoter of SLC7A11 to suppress its transcription and thereby result in lipid peroxidation and ferroptosis after the stimulation with erastin. 50 Consistent with previous reports, our data showed that both the mRNA and protein levels of ATF3 were significantly increased in response to either erastin/ RSL3 monotreatment, and were further upregulated after combined treatment with IFN-γ in melanoma cells (figure 7B,C). Chromatin immunoprecipitation assay showed more enrichment of ATF3 to the promoter of miR-21-3p on the treatment with erastin/RSL3, which was forwardly potentiated after combined treatment with IFN-γ (figure 7D).…”
Section: Mir-21-3p Increases the Efficacy Of Anti-pd-1 Immunotherapy ...mentioning
confidence: 99%
“…Endoplasmic reticulum stress promotes the upregulation of ATF3, which increases intracellular H 2 O 2 levels through two pathways: ATF3 activates NOX4 transcription, overproduces of superoxide, inhibits SLC7A11 transcription, and deplets cysteine and GSH. H 2 O 2 increases intracellular Fe 2+ and restricts synthesis of GSH, leading to a continuous accumulation of toxic intracellular lipid peroxides ( Lu et al, 2021 ).…”
Section: Other Transcription Factorsmentioning
confidence: 99%